Avaliação de técnicas de defumação para mexilhão Perna perna: análise sensorial e rendimento - Coelho Emerenciano, Mauricio Gustavo [UNESP]; de Rodrigues de Souza, Maria Luiza; Franco, Nilson do Prado (Inst Pesca, 2008)
The objective of the present work was evaluate two techniques of smoking, the hot traditional and with use of smoke natural aroma or "liquid smoke", having as control Perna perna mussels vapor cooked. Sensorial characteristics were appraised (appearance, color, aroma, texture, flavor and salt tenor) and yield processing. The experimental design was completely randomized with three treatments (T1 = smoked with liquid smoke; T2 = traditional smoked and T3 = just cooked, control), with nine repetitions. For sensorial analysis 30 people were used, where each one was considered a block. There was significant difference for processing performance among treatments (P<0.05), however there was not significant difference independent of smoked technique applied. Nevertheless, smoking technique using smoke natural aroma was more attractive, presenting better results with relationship to sensorial characteristics and final product packaged for commercialization.
Evaluation of smoking techniques for Perna perna mussels: sensorial analysis and yield
Keywords: mussels; smoking; liquid smoke; yield; Perna perna; sensorial characteristics